Development of a next-generation chikungunya virus vaccine based on the HydroVax platform. - Dawn K Slifka; Hans-Peter Raué; Whitney C Weber; Takeshi F Andoh; Craig N Kreklywich; Victor R DeFilippis; Daniel N Streblow; Mark K Slifka; Ian J Amanna (PLoS Pathogens)
Chikungunya virus (CHIKV) is an emerging/re-emerging mosquito-borne pathogen responsible for explosive epidemics of febrile illness characterized by debilitating polyarthralgia and the risk of lethal infection among the most severe cases. Despite the public health risk posed by CHIKV, no vaccine is currently available. Using a site-directed hydrogen peroxide-based inactivation approach, we developed a new CHIKV vaccine, HydroVax-CHIKV. This vaccine technology was compared to other common virus inactivation approaches including β-propiolactone (BPL), formaldehyde, heat, and ultraviolet (UV) irradiation. Heat, UV, and BPL were efficient at inactivating CHIKV-181/25 but caused substantial damage to neutralizing epitopes and failed to induce high-titer neutralizing antibodies in vaccinated mice. HydroVax-CHIKV and formaldehyde-inactivated CHIKV retained intact neutralizing epitopes similar to live virus controls but the HydroVax-CHIKV approach demonstrated a more rapid rate of virus inactivation. HydroVax-CHIKV vaccination induced high neutralizing responses to homologous and heterologous CHIKV clades as well as to other alphaviruses including Mayaro virus, O'nyong'nyong virus, and Una virus. Following heterologous infection with CHIKV-SL15649, HydroVax-CHIKV-immunized mice were protected against viremia, CHIKV-associated arthritic disease, and lethal CHIKV infection by an antibody-dependent mechanism. In contrast, animals vaccinated with Heat- or UV-inactivated virus showed no protection against viremia in addition to demonstrating significantly exacerbated CD4+ T cell-mediated footpad swelling after CHIKV infection. Together, these results demonstrate the risks associated with using suboptimal inactivation methods that fail to elicit protective neutralizing antibody responses and show that HydroVax-CHIKV represents a promising new vaccine candidate for prevention of CHIKV-associated disease.